Design and Photoelectric Performance of Perfect Solar Absorber Based on GaAs Grating - Liu, Bin; Wu, Pinghui; Li, Yan; Zhu, Hongyang; Lv, Li (Frontiers in Materials, 2022)
In recent years, solar energy has received extensive attention as a clean and renewable energy. We present a perfect broadband solar absorber based on tungsten and semiconductor GaAs in this paper. The structure of GaAs grating-GaAs film-W substrate has been proposed. And the finite time domain difference method (FDTD) has been used for the numerical simulation of the model. Broadband absorption has been realized in the 500–1,850 nm, by adjusting the parameters of geometry to excite high-efficiency surface plasmon resonance. The absorption spectrum of the structure can be changed by adjusting the geometric parameters to meet different needs. The proposed absorber has incidence insensitive (0–60°) and high short-circuit current characteristics. The structure is simple and easy to manufacture, and has superior photoelectric properties to be application in photothermal conversion, collection and utilization of solar energy.